Integrated Observations and Informatics Improve Understanding of Changing Marine Ecosystems - Benson, Abigail; Brooks, Cassandra M.; Canonico, Gabrielle; Duffy, Emmett; Muller-Karger, Frank; Sosik, Heidi M.; Miloslavich, Patricia; Klein, Eduardo (Frontiers in Marine Science, 2018)
Marine ecosystems have numerous benefits for human societies around the world and many policy initiatives now seek to maintain the health of these ecosystems. To enable wise decisions, up to date and accurate information on marine species and the state of the environment they live in is required. Moreover, this information needs to be openly accessible to build indicators and conduct timely assessments that decision makers can use. The questions and problems being addressed demand global-scale investigations, transdisciplinary science, and mechanisms to integrate and distribute data that otherwise would appear to be disparate. Essential Ocean Variables and marine Essential Biodiversity Variables, conceptualized by the Global Ocean Observing System and the Marine Biodiversity Observation Network, respectively, guide observation of ocean. Additionally, significant progress has been made to coordinate efforts between existing programs, such as the Global Ocean Observing System, Marine Biodiversity Observation Network, and Ocean Biogeographic Information System collaboration agreement. Globally and nationally relevant indicators and assessments require increased data sharing and sharing of analytical methods, sustained long-term and large-scale observations, and resources to dedicated to these tasks. We propose a vision and key tenets as a guiding framework for building a global integrated system for understanding marine biological diversity and processes to address policy and resource management needs. This framework includes: using Essential Ocean Variables and Essential Biodiversity Variables and implementing the principles of FAIR data and action ecology. In doing so, we can encourage relevant, rapid, and integrative scientific advancement that can be implemented by decision makers to maintain marine ecosystem health.